2014
DOI: 10.1002/tox.22016
|View full text |Cite
|
Sign up to set email alerts
|

Involvement of L‐type Ca2+ channel and toll‐like receptor‐4 in nickel‐induced interleukin‐8 gene expression

Abstract: The metal nickel (Ni(2+)) is found everywhere in our daily lives, including coins, costume jewelry, and even nuts and chocolates. Nickel poisoning can cause inflammatory reactions, respiratory diseases, and allergic contact dermatitis. To clarify the mechanism by which nickel induces mediators of inflammation, we used the human acute monocytic leukemia THP-1 cell line as a model. Interleukin (IL)-8 promoter activity as well as gene expression were tested by luciferase assay and real-time polymerase chain react… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
8
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 37 publications
2
8
0
Order By: Relevance
“…The potential underlying mechanism of such nickel‐induced IL‐8 production could be that described by Lin and coworkers in 2016. They postulated an ‘IL‐8 gene expression via the L‐type Ca(2+) channel, Toll‐like receptor‐4 (TRL‐4) and nuclear factor NF‐κB signal transduction pathways’ . This would be in accordance with results published by Tsou et al .…”
Section: Discussionsupporting
confidence: 77%
“…The potential underlying mechanism of such nickel‐induced IL‐8 production could be that described by Lin and coworkers in 2016. They postulated an ‘IL‐8 gene expression via the L‐type Ca(2+) channel, Toll‐like receptor‐4 (TRL‐4) and nuclear factor NF‐κB signal transduction pathways’ . This would be in accordance with results published by Tsou et al .…”
Section: Discussionsupporting
confidence: 77%
“…These results indicate that nickel-induced Th17 cell development is dependent on the production of IL-23 by human monocyte-derived dendritic cells via toll-like receptor 4 (TLR4), p38 MAPK, NF-jB and Jak-signal transducer and activator of transcription pathways. Similar observations on TLR4 and NF-jB involvement were made by Zoroddu et al (2014), Lin et al (2016), Oblak et al (2015) and Peana et al (2017). Almogren et al (2013) observed a predominance of a Th1 phenotype, based on cytokine expression including IL-4 and IL-10, of lymphocytes collected from patients suffering from nickel allergy, in line with commonly accepted mechanisms of contact sensitivity.…”
Section: Immunotoxic Activity Of Nickelsupporting
confidence: 82%
“…The role of extracellular-and calcium-dependent mechanisms has also been proposed in other reports on toxicity of Ni. For example, a study using THP-1 cells to investigate mechanisms for Ni-induced changes on IL-8 gene expression demonstrated the role of an extracellular mechanism via TLR-4 and the L-type Ca 2+ channel, followed by the downstream extracellular signal-regulated kinases (ERKs) and NF-κB signaling pathways [27]. Indeed, ERK/MAPK signaling was predicted in the IPA analysis for Ni NPs and NiCl 2 in our study ( Figure 5).…”
Section: Discussionmentioning
confidence: 99%